The politics of the coffee economy: the conflicts between the republican oligarchies in Taubaté’s Convention Project - Vioto de Andrade, Caio César (Revista Crítica Histórica, 2020)
This paper intends to deal with the approval process of the Taubaté Convention, in 1906, during the Rodrigues Alves government, which sought to solve the crisis generated by the fall in international coffee prices, the country’s main export product since at least 1895. Towards the history of the politics, from Rosanvallon (2010), we consider the idea of "history making itself" that deals with how social and political actors understand a situation and how the political scope is permeated in modernity by tensions and conflicts, from which emanate social reflections and transformations, starting from political activity. In this way, we consider that the intervention of the State in the coffee economy, symbolized by the Convention, was not only an economic inevitability, but a political choice, after intense conflicts within the most important oligarchies of the First Republic, especially that of Sao Paulo, the main interested in the coffee valorization, and which conflicted with the President of the Republic, hesitant about the project.